Chloroplast redox imbalance governs phenotypic plasticity: the “grand design of photosynthesis” revisited - Huner, Norman; Dahal, Keshav; Hollis, Lauren; Bode, Rainer; Rosso, Dominic; Krol, Marianna; Ivanov, Alexander G. (Frontiers in Plant Science, 2012)
Sunlight, the ultimate energy source for life on our planet, enters the biosphere as a direct consequence of the evolution of photoautotrophy. Photoautotrophs must balance the light energy absorbed and trapped through extremely fast, temperature-insensitive photochemistry with energy consumed through much slower, temperature-dependent biochemistry and metabolism. The attainment of such a balance in cellular energy flow between chloroplasts, mitochondria and the cytosol is called photostasis. Photoautotrophs sense cellular energy imbalances through modulation of excitation pressure which is a measure of the relative redox state of QA, the first stable quinone electron acceptor of PSII reaction centers. High excitation pressure constitutes a potential stress condition that can be caused either by exposure to an irradiance that exceeds the capacity of C, N and S assimilation to utilize the electrons generated from the absorbed energy or by low temperature or any stress that decreases the capacity of the metabolic pathways downstream of photochemistry to utilize photosynthetically-generated reductants. The similarities and differences in the phenotypic responses between cyanobacteria, green algae, crop plants and variegation mutants of Arabidopsis thaliana as a function of cold acclimation and photoacclimation are reconciled in terms of differential responses to excitation pressure and the predisposition of photoautotrophs to maintain photostasis. The various acclimation strategies associated with green algae and cyanobacteria versus winter cereals and Arabidopsis thaliana are discussed in terms of retrograde regulation and the “grand design of photosynthesis” originally proposed by Daniel Arnon in 1982.